Pengaruh Permainan Wassimni Terhadap Pemerolehan Kosa Kata Bahasa Arab Pada Siswa Kelas VII MTs. Nurussaleh Bangkalan - Faruq Abdul Muid; firdausi nurharini; Muhammad Abdus Salam (Program Studi Pendidikan Bahasa Arab Sekolah Tinggi Bahasa Arab dan Dakwah Masjid Agung Sunan Ampel Surabaya, 2022)
This study aims to determine whether there is an increase in students before or after being given the Wassimni game treatment on Arabic vocabulary acquisition. It is assumed that there is a significant difference, as formulated in the research hypothesis that there is a significant difference in increasing Arabic vocabulary acquisition by using the Wassimni game to support Arabic vocabulary acquisition. The sample taken by the researchers amounted to 32 students. Data was collected by using the methods of interviews, observation, experiments, documentation, and tests. So far, the process of learning Arabic in class VII MTs. Nurussaleh Bangkalan for acquiring Arabic vocabulary is carried out by means of qira'ah. So the researcher, to increase the acquisition of Arabic vocabulary by using the Wassimni game. The aims of this study are (1) to identify and describe the implementation of Wassimni game learning to improve the ability to acquire Arabic vocabulary in seventh grade students of MTs. Nurussaleh Bangkalan Nurussaleh Bangkalan. (2) To determine the effect of the Wassimni game on the acquisition of Arabic vocabulary in class VII MTs. Nurussaleh Bangkalan students. Nurussaleh Bangkalan. It can be seen that the Wassimni game on Arabic vocabulary acquisition is increasing. Which in the Pre-Test VII graders were at intervals of 40-54 totaling 9 people, after doing the Post-Test VII graders of MTs. Nurussaleh Bangkalan. were at intervals of 85-100 with a total of 23 people from 32 students of MTs. Nurussaleh Bangkalan.